Związek między przejawianym stylem poczucia humoru a prezentowaną postawą rodzicielską - Piasecka, Anita; Gryz, Monika; Łuczak, Weronika; Mikajewska, Adrianna; Kleka, Paweł (Człowiek i Społeczeństwo, 2021)
The aim of the present study was to examine the relationship between styles of sense of humour and parental attitude. The study sample consisted of adults who are parents, mostly women (59 vs 14 men). Because the study was exploratory in nature, a statistical significance level of α < .10 was adopted and tentatively demonstrated the existence of partial relationships between the constructs analyzed. Level of self-deprecating humour correlates with intensity of demanding attitude (rho = .249, p = .035) and intensity of demanding attitude (rho = .241, p = .042). In contrast, the level of aggressive humor correlates negatively with accepting attitude (rho = –.273, p = .012) but correlates positively with inconsistent attitude intensity (rho = .217, p = .067).